Implementation Of Weighted Product Method In Cadre Selection At Sawah Lebar Community Health Center Bengkulu - Anggraini, Reren; Sari, Herlina Latipa; Sudarsono, Aji (Jurnal Media Computer Science, 2025)
Sawah Lebar Health Center Bengkulu faces challenges in selecting health cadres who have the right qualifications and abilities to support health programs in the community. Selecting the right cadres is an important factor in improving the quality of health services at the basic level. One method that can be used to assist in this selection process is the Weighted Product (WP) method. This method is used to perform objective calculations and assessments based on predetermined criteria, such as education level, work experience, communication skills, and commitment to health programs.The purpose of this study was to implement the Weighted Product method in selecting cadres at Sawah Lebar Health Center Bengkulu and to evaluate the most relevant criteria in selecting the right cadres. In addition, this study aims to test the effectiveness of the system built using the WP method in providing optimal cadre recommendations.The method used in this study is to collect data on cadre candidates, then assess each candidate based on the weight and criteria that have been determined. The results of the system test show that the use of the WP method can produce objective cadre selection, reduce subjectivity in decision making, and increase transparency in the selection process. In the system testing, this system successfully provided results that were in accordance with the expectations and priorities of the Health Center in selecting cadres.In conclusion, the application of the Weighted Product method can improve the accuracy and objectivity in selecting cadres at the Sawah Lebar Bengkulu Health Center. The system that was built has also proven effective in providing recommendations for cadres that are in accordance with the established criteria, so that it can support the success of health programs in the region.